Cu-catalyzed direct C1–H trifluoromethylation of pyrrolo[1, 2-a]quinoxalines. (22nd January 2022) - Li, Yang; Liu, Yali; Hao, Di; Li, Chuntian; Liu, Yan; Gu, Yanlong; Vaccaro, Luigi; Liu, Ping
Abstract: An efficient Cu(II)-catalyzed direct C–H trifluoromethylation of pyrrolo[1, 2- a ]quinoxalines with CF3 SO2 Na in the presence of K2 S2 O8 as an oxidant has been developed. A variety of C1-trifluoromethylated pyrrolo[1, 2- a ]quinoxalines can be obtained with moderate to good yields. Broad substrate range, excellent regioselectivity, and gram-scale synthesis are key features of this reaction. The further modification of the trifluoromethylated product is also investigated. Controlled experiments showed that the trifluoromethylation process may involve a CF3 -radical mechanism. Graphical abstract: Image 1 Highlights: An efficient Cu(II)-catalyzed direct C–H trifluoromethylation of pyrrolo[1, 2- a ]quinoxalines with CF3 SO2 Na is established. A variety of C1-trifluoromethylated pyrrolo[1, 2- a ]quinoxalines is obtained. The trifluoromethylation process may involve a CF3 -radical mechanism.